Female CEO and firm performance in Vietnamese family business - Truong, Khiem Dieu (Asian Economic and Financial Review, 2025)
This study examines the relationship between female CEOs and the performance of firms in the family business. The study uses 137 Vietnamese-listed family businesses on the Ho Chi Minh Stock Exchange from 2010 to 2022. The study indicates that the external female CEO is less likely to impact the financial performance of a business family because of their control over family members. On the other hand, the financial performance of the family business is significantly influenced by the relationship between the female CEO heir and the female CEO founder. The result of the study is consistent with the upper echelon theory and double standards of competence theory. Furthermore, the study employs the 2SLS model to strengthen the findings in situations involving endogenous factors. The result of 2SLS reconfirms the role of the internal female CEO in the family business, which indicates that there is a positive relation between the internal CEO and financial performance in the family business. Otherwise, there is no relationship between the external CEO and financial performance in the family business. The study illuminates the significance of gender diversity in the top-tier positions within family businesses. The result of the study contributes to the practical implications for the government, firms, and investors.